Isolation and identification of an antibacterial compound in sea grapes (Caulerpa chemnitzia (Esper) J.V. Lamouroux) - Latona, Charmelie G.; Veronica Julia G.; Toralba, Joanna V.
Antibiotics kill or inhibit bacterial growth that causes infectious diseases, drastically changing modern medicine. Unfortunately, the increasing trend in bacterial drug resistance and the decreasing trend in the discovery of antibiotics prompt researchers to find alternative sources of novel secondary metabolites. While most bioactive compounds originate from terrestrial sources, the vast marine ecosystem remains largely unexplored. As a marine biodiversity hub, the Philippines houses a variety of marine organisms such as seaweeds and sea grapes. Caulerpa chemnitzia, one of the green seaweeds of the Caulerpa species wildly abundant in La Union, was reported to have potential antibacterial activity. The study aimed to identify the antibacterial compound/s in C. chemnitzia against Staphylococcus aureus subsp. aureus ATCC 29213.